Effect of circuit training on physical fitness among fifth-grade male elementary school students - inda Lestari; Ewan Irawan; Nasrullah; Anas Ardiansyah; Andy Eddy (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2026)
This study was motivated by the low level of physical fitness among elementary school students, which impacts their learning ability and participation in physical activities; therefore, effective teaching methods are needed, one of which is circuit training. This study aims to analyze the effect of the circuit training method on the physical fitness levels of fifth-grade students at SDN Inpres Sampungu. The study employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest design, involving a sample of 15 male students selected via purposive sampling. The instrument used was the Indonesian Physical Fitness Test (TKJI), which included a 40-meter run, pull-ups, sit-ups, vertical jump, and a 600-meter run, with circuit training administered over 8 sessions. The results of the study showed a significant increase in the average physical fitness score from 10.7 on the pretest to 20.1 on the posttest. The results of the paired sample t-test showed a t-value of -36.9 with a significance level of p < 0.001, indicating a highly significant difference between pre- and post-intervention scores. Thus, circuit training has been proven effective in significantly improving students’ physical fitness.